Quick Reference Guide to Preemergence/Residual Herbicides for Citrus Weed Control - R. Kanissery; W. Liu; J. D. Burrow; S. H. Futch; B. A. Sellers; S. S. Teems (EDIS, 2022)
The 2-page document intends to provide readers with quick information (mode of action, weeds controlled, postharvest interval, usage restrictions, suggested rates, etc.) on different preemergent or soil-residual herbicides used in citrus. Compiled by R. Kanissery, W. Liu, J. D. Burrow, S. H. Futch, B. A. Sellers, and S. S. Teems and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1438